Bumblebees’ orofacial reactions to tastes provide evidence for affective evaluation - Yonghe Zhou; Thomas Ingraham; Andrew B. Barron; Fei Peng; Cwyn Solvi (Proceedings of the National Academy of Sciences, 2026)
Facial expressions provide a critical window into the internal states of animals, allowing the identification of affective processes and their underlying neural mechanisms. In mammals, postconsumption orofacial reactions—such as tongue protrusions to sweet tastes—are among the most robust and widely accepted behavioral markers of positive hedonic impact (liking), distinct from motivation (wanting). However, no equivalent markers have been established in insects, leaving their capacity for affective evaluation unresolved. Here, we show that bumblebees exhibit discrete orofacial reactions that are functionally analogous to those described in mammals. Bees displayed postconsumption glossa protrusions to rewarding solutions and head-shaking and mouth-wiping to aversive tastes. These reactions were not tied to any specific taste identity. Behavioral and pharmacological experiments demonstrated that glossa protrusions did not automatically occur due to consumption, were independent of ongoing feeding mechanisms and dopamine-mediated motivation, and were enhanced by the endocannabinoid anandamide. Our findings support postconsumption glossa protrusions as a fast, reliable, and evolutionarily comparable candidate behavioral marker of affective evaluation in an invertebrate. By providing evidence that a behavior which tracks liking can be dissociated from motivational (wanting) responsiveness in bumblebees, this work establishes an experimental framework for investigating the neural basis and evolutionary origins of affective processing. More broadly, these results open the door to rigorous cross-phyletic approaches to emotion.